Association of low muscle mass index and sarcopenic obesity with knee osteoarthritis: a systematic review and meta-analysis - Qiming Wu; Zhuyan Xu; Xiaomin Ma; Juan Li; Jun Du; Jing Ji; Xiaomeng Ling; Juntao Kan; Min Zhao (Journal of the International Society of Sports Nutrition)
Background Sarcopenia and knee osteoarthritis are common age-related diseases that have become important public health issues worldwide. Few studies have reported the association between muscle mass loss and knee osteoarthritis. This may be due to the high level of heterogeneity between studies stemming from different definitions of muscle mass loss.Methods The systematic searches were carried out in PubMed and Web of Science from the inception of the databases until 13 January 2023, by two independent researchers. Pooled odds ratios (ORs) for overall and subgroup analyses were obtained using either a random effects model (I2 >50%) or fixed effects model (I2 ≤50%) in Stata.Results Of the 1,606 studies identified, we ultimately included 12 articles on the association between muscle mass and knee osteoarthritis (prospective: n = 5; cross-sectional: n = 7). Low-quality evidence indicated that low muscle mass index and sarcopenic obesity increase the odds of knee osteoarthritis (low muscle mass index OR: 1.36, 95% CI: 1.13–1.64; sarcopenic obesity OR: 1.78, 95% CI: 1.35–2.34). However, no association was observed between general sarcopenia or low muscle mass with knee osteoarthritis.Conclusion This systematic review and meta-analysis revealed that low muscle mass index and sarcopenic obesity were associated with an increased risk of developing knee osteoarthritis.